Classification of frequency response areas in the inferior colliculus reveals continua not discrete classes. (12th July 2013) - Palmer, Alan R.; Shackleton, Trevor M.; Sumner, Christian J.; Zobay, Oliver; Rees, Adrian
Key points Neurons in the auditory midbrain, the inferior colliculus, are selectively sensitive to combinations of sound frequency and level as illustrated by their frequency/level receptive fields. Different receptive field shapes have been described, but we do not know if these represent discrete classes reflecting afferent inputs from individual sources, or a more complex pattern of integration. In this study we used objective methods to analyse the receptive fields of over 2000 neurons in the guinea pig inferior colliculus. Subjectively we identified seven different receptive field classes, but objectively these classes formed continua with many neurons having receptive field shapes intermediate to these extremes. These findings are consistent with neurons receiving inhibitory inputs of different strength and frequency disposition but not consistent with neurons reflecting inputs only from individual brainstem nuclei. These results are important for understanding the functional organisation of the inferior colliculus and its role in auditory processing. Abstract A differential response to sound frequency is a fundamental property of auditory neurons. Frequency analysis in the cochlea gives rise to V‐shaped tuning functions in auditory nerve fibres, but by the level of the inferior colliculus (IC), the midbrain nucleus of the auditory pathway, neuronal receptive fields display diverse shapes that reflect the interplay of excitation and inhibition. The origin and nature of these frequency receptive field types is still open to question. One proposed hypothesis is that the frequency response class of any given neuron in the IC is predominantly inherited from one of three major afferent pathways projecting to the IC, giving rise to three distinct receptive field classes. Here, we applied subjective classification, principal component analysis, cluster analysis, and other objective statistical measures, to a large population (2826) of frequency response areas from single neurons recorded in the IC of the anaesthetised guinea pig. Subjectively, we recognised seven frequency response classes (V‐shaped, non‐monotonic Vs, narrow, closed, tilt down, tilt up and double‐peaked), that were represented at all frequencies. We could identify similar classes using our objective classification tools. Importantly, however, many neurons exhibited properties intermediate between these classes, and none of the objective methods used here showed evidence of discrete response classes. Thus receptive field shapes in the IC form continua rather than discrete classes, a finding consistent with the integration of afferent inputs in the generation of frequency response areas. The frequency disposition of inhibition in the response areas of some neurons suggests that across‐frequency inputs originating at or below the level of the IC are involved in their generation.